Area estimation of peninsular Malaysia by Numerical methods / Siti Nuruljannah Mohamed Zeinnudin and Nurul Kamaliah Omar - Mohamed Zeinnudin, Siti Nuruljannah; Omar, Nurul Kamaliah (2019)
In Mathematics, area is defined as the measurement of how much space is taken up on a 2D surface and is expressed in square units. In area calculation, it is divided into two which are the area of regular and irregular shapes. Regular shapes have their own formulas which made it very easy to get the exact value of area accurately. Irregular shapes can be calculated using integration given when the function is known. However, when the function is not given, numerical methods can be applied. Some of the numerical methods that can be used are Trapezoidal, Simpson’s 1/3, Simpson 3/8, Boole’s, Weddle’s, Durand’s and Hardy’s Rule. These methods are quite simple but they possess some error to be compared with the exact value.